2021
DOI: 10.1002/smll.202102089
|View full text |Cite
|
Sign up to set email alerts
|

Erbium Single Atom Composite Photocatalysts for Reduction of CO2 under Visible Light: CO2 Molecular Activation and 4f Levels as an Electron Transport Bridge

Abstract: It is still challenging to design a stable and efficient catalyst for visible‐light CO2 reduction. Here, Er3+ single atom composite photocatalysts are successfully constructed based on both the special role of Er3+ and the special advantages of Zn2GeO4/g‐C3N4 heterojunction in the photocatalysis reduction of CO2. Especially, Zn2GeO4:Er3+/g‐C3N4 obtained by in situ synthesis is not only more conducive to the tight junction of Zn2GeO4 and g‐C3N4, but also more favorable for g‐C3N4 to anchor rare‐earth atoms. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The authors have attributed the greatly improved photocatalytic activity of MOF-525-Co to the boosted separation efficiency of electron-hole pairs in porphyrin units after the Co introduction. Since then, many research works of photocatalytic CO 2 reduction into CO or CH 4 fuel gas have been reported over various single-atom photocatalysts along with the production of H 2 , where H 2 O provides the hydrogen resource 59,[74][75][76]114,[155][156][157][158][159][160][161][162][163][164][165][166]. Li et al have created a unique Fe-N 4 O site supported on nitrogen-rich carbon for photocatalytic CO 2 reduction via a facile top-down strategy (Figures 10A-…”
mentioning
confidence: 99%
“…The authors have attributed the greatly improved photocatalytic activity of MOF-525-Co to the boosted separation efficiency of electron-hole pairs in porphyrin units after the Co introduction. Since then, many research works of photocatalytic CO 2 reduction into CO or CH 4 fuel gas have been reported over various single-atom photocatalysts along with the production of H 2 , where H 2 O provides the hydrogen resource 59,[74][75][76]114,[155][156][157][158][159][160][161][162][163][164][165][166]. Li et al have created a unique Fe-N 4 O site supported on nitrogen-rich carbon for photocatalytic CO 2 reduction via a facile top-down strategy (Figures 10A-…”
mentioning
confidence: 99%
“…Rare‐earth metals also show broad application prospects in CO 2 reduction 194 . Wang et al 195 prepared a single‐atom Er 3+ composite photocatalyst (Zn 2 GeO 4 :Er 3+ /g‐C 3 N 4 ), and without a sacrificial agent, the photocatalytic efficiency is five times higher than that of g‐C 3 N 4 . Through XPS and DFT, the authors proved that the 4f energy level of Er 3+ can serve as an electron transfer bridge at the interface between Zn 2 GeO 4 and g‐C 3 N 4 , thereby promoting the activation of CO 2 (Figure 14F).…”
Section: Applications Of Single‐atom Catalysts In Carbon Neutralmentioning
confidence: 99%
“…Rare-earth metals also show broad application prospects in CO 2 reduction. 194 Wang et al 195 prepared a single-atom Er 3+ composite photocatalyst (Zn 2 GeO 4 :Er 3+ / g-C 3 N 4 ), and without a sacrificial agent, the photocatalytic efficiency is five times higher than that of g-C 3 N 4 .…”
Section: Carbon Dioxide Reductionmentioning
confidence: 99%
“…Similarly, Ag, Au, Pt, Co and Er SAs supported by g-C 3 N 4 , MOFs/covalent organic frameworks (COFs), TiO 2 , CdS and other semiconductor nanomaterials could boost the photocurrent density and the total photocatalytic performance compared to their counterparts without single metal active sites. 30,49,[75][76][77][78][79][80][81][82][83] From these few cases, SACs have demonstrated their potentials in PEC applications. The rational deployment and fundamental investigation of SACs in PEC deserve further study.…”
Section: Progress Of Sacs For Photoelectrocatalysismentioning
confidence: 99%